Efektivitas Konsumsi Tablet Fe Selama Menstruasi Terhadap Peningkatan Kadar Hemoglobin Pada Mahasiswi D-III Kebidanan Universitas Pasir Pengaraian. - Sepduwiana, Heny (Jurnal Martenity and Neonatal, 2017)
Along age reproduktif women will undergo menstruation , and the blood out in a the period of menstruating an average of about 50 cc and blood will lose iron of 12,5-15 mg per month , or similar to 0,4-0,5 mg a day .One strategy to increase intake fe are they consume suplementasi fe .When iron in the blood below normal will lead to anemia .Anemia is a the state of when the number of red blood cells or the amount of hemoglobin under normal .Prevalence of anemia in indonesia, which is 21.7 % , with the proportion of 20.6 % in urban and 22,8 % in rural .By age group , patients anemia was 5-14 years amounting to 26,4 % of 18,4 % in age group of 15-24 years old .The purpose of this research is to find the effectiveness of consumption tablet fe during menstruation to elevated levels of hemoglobin in a student of d-iii obstetrics university sand pengaraian. The kind of research quantitative analytic to the research used is praeksperimen and approach one group pretest posttest.The population and sample in research it is a whole a student of level i and ii prodi d-iii obstetrics university sand pengaraian who total of 24 respondents.Tekhnik the sample collection use of sampling saturated.The results of the study the average levels hemoglobin on measuring pre-test is 11,8 gr / dl with standard deviations 1.4 gr / dl.On measuring post-test obtained the average levels hemoglobin is 13.9 gr / dl with standard deviations 1.2 gr / dl. Look its mean value the difference between pre-test and post-test is -2,1 gr / dl with standard deviations 1.7 gr / dl.The results of statistical tests obtained value p = 0.0001 ( & lt; 0,005 ).Conclusion there was a correlation consumption tablet fe during menstruation to elevated levels of hemoglobin.Advice to the institution university education sand pengaraian it is hoped the result this research can be used as as a source of informa.